COMPLEMENT ACTIVATION IN MULTIPLE SCLEROSIS AND NMO SPECTRUM DISORDERS. Issue 12 (15th November 2016) - Luppe, Sebastian; Hakobyan, Svetlana; Evans, David; Harding, Katherine; Loveless, Sam; Robertson, Neil; Morgan, B. Paul
Abstract : MS and NMOSD are inflammatory CNS diseases and early manifestations can be similar creating management problems, since MS drugs may be ineffective and/or worsen NMOSD. MR imaging and AQP4-Abs provide diagnostic information in most NMOSD cases, but a minority remain AQP4-Ab-negative; underlining the need for alternative diagnostic biomarkers. Complement (C) activation is a core pathological feature in both. We have investigated whether plasma C analytes can distinguish MS from NMOSD. Plasma from 53 NMOSD, 49 MS and 69 controls was tested in 2 multiplex assays: the first measuring 5 C activation products and the second comprising 5 C proteins. All activation products were significantly elevated in NMOSD compared to control or MS, particularly in AQP4-Ab-positive samples. Four C proteins (C1inh, C1s, C5, FH) were significantly higher in NMOSD (notably AQP4-Ab-positive) compared to MS or controls, whilst one (C3) was significantly lower. Receiver operating characteristic curves for each comparator identified best distinguishing analytes; a model developed from the most predictive gave an area under the curve of 0.938 for NMOSD versus controls and 0.977 for NMOSD versus MS. These data demonstrate NMOSD is characterised by significant C activation and C3 consumption, and a subset of C analytes could provide a supplementary tool for diagnosis.